Penerapan Metode Posenet untuk Deteksi Ketepatan Pose Yoga - Raynaldi Ahmad Asshidiqy; Agus Setiawan; Dimas Sasongko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
When someone does yoga activities, usually, someone follows yoga guidelines in the form of yoga classes and yoga self-guidance, which is usually in the form of images, videos, and audio. But along with the rapid development of technology, now there are many yoga guides and easy to get. Yoga activities can now be done independently without approaching a yoga instructor. The purpose of this study is to help yogis to be able to do yoga correctly and to follow yoga guidelines with the correct poses with a system that contains yoga poses and also as the main feature of correcting yoga poses that yogis do to get yoga poses correctly. The resulting system will capture yoga poses and detect whether the pose is correct according to the yoga pose guidelines. Based on the verification of the distance between the device or the device that has a camera, it is placed at a distance of 200cm – 250cm between the device and the yogis. The device's height is placed in a place that has a height half the size of the yogi's whole body or at the height of 85cm. The test results using the BlackBox method get no errors. Besides that, the system can run well in a room with 7-watt LED lights, and no objects block the yogis, so the camera catches the whole body.